TELAAH SEMANTIK KOSAKATA BAHASA INDONESIA PESERTA DIDIK KELAS IX MTs, HUSNUL KHATIMAH KHUSUS YANG BERLATAR BELAKANG BAHASA MANDAR - Khusnul KKhatimah; Madinah Madinah (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2016)
Subjects of this study was set at 22 orang.Penarikan subjects in this study using the technique of multiple-choice test, which means that the determination of the subject is done deliberately by the number of representative class penelitian.Teknik in data collection in this study is done through techniques tes.Selanjutnya collected data is analyzed using descriptive statistical techniques kualitatif.Dalam process research shows that mastery of semantics vocabulary Indonesian students of class IX MTs special Khusnul speaking backgrounds Mandar inadequate. This is evidenced from the number of students who received grades 75 up as the standard of mastery learning is applied in this study sekolah.Dari submitted suggestions as follows: 1) should the IX grade students more carefully consider the explanations of the subject teachers, especially those on the understanding of the vocabulary; 2) The learners should be given the task of communicating raised the use of new terms; 3) To support the learning process should have a dictionary vocabulary or dictionary terms that are popular; 4) In the understanding of vocabulary or terms should learners in learning, not just fields of study Indonesian but other subject areas also need to be planting new terms.